The International Encyclopedia of Organizational Communication 2017
DOI: 10.1002/9781118955567.wbieoc052
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing

Abstract: Crowdsourcing is an online, distributed problem solving and production model where organizations tap the collective intelligence of online communities. A joining of top‐down management processes with bottom‐up open innovation processes, crowdsourcing can be used by organizations to solve four general types of problems related to information management or ideation. Crowds are motivated in a variety of ways and often consist of professionals or experts who self‐select into a given challenge, giving rise in recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…In the last decade, many organizations have turned to crowdsourcing to engage with consumers, accelerate their innovation cycles, to search for new ideas, and to create knowledge (Afuah & Tucci, 2012;Majchrzak et al 2012;Bayus 2013;Brabham 2013a). As crowdsourcing has become an increasingly popular method for business organizations to gather IT-mediated input from individuals, the phenomenon has also spread to non-commercial contexts too.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, many organizations have turned to crowdsourcing to engage with consumers, accelerate their innovation cycles, to search for new ideas, and to create knowledge (Afuah & Tucci, 2012;Majchrzak et al 2012;Bayus 2013;Brabham 2013a). As crowdsourcing has become an increasingly popular method for business organizations to gather IT-mediated input from individuals, the phenomenon has also spread to non-commercial contexts too.…”
Section: Introductionmentioning
confidence: 99%
“…In this definition the author also points to an unknown group of users. The definition suggests that he limits crowdsourcing to problem solving, however he understands this in a very broad sense: creating new products, seeking consensus in social issues, processing large data sources, or explaining difficult scientific problems (Brabham, 2013). In the author's opinion not every online community should be perceived as a crowdsourcing one.…”
Section: Conceptualisation Of Crowdsourcing On the Basis Of Managemenmentioning
confidence: 99%
“…Crowdsourcing has emerged in the last decade as an important subject in the field of management (Howe, 2006;Brabham, 2013). Nonetheless, on the basis of management sciences it is a relatively new, but simultaneously a highly up-to-date area of scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…Government, motivated by the multiple success stories of 'crowdsourcing' in the private sector [3,4,18,19,29] has started moving in this direction as well, and this gives rise to the gradual development of the 'citizen-sourcing' [12, 17, 21-22, 26-28, 32-35]. Crowd-sourcing is defined as 'a new web-based business model that harnesses the creative solutions of a distributed network of individuals, in order to exploit 'collective wisdom' and mine fresh ideas from large numbers of individuals' [4].…”
Section: Introductionmentioning
confidence: 99%
“…Crowd-sourcing is defined as 'a new web-based business model that harnesses the creative solutions of a distributed network of individuals, in order to exploit 'collective wisdom' and mine fresh ideas from large numbers of individuals' [4]. Previous management research and practice has revealed the high potential of a diverse 'crowd' of individuals to provide a wealth of information and knowledge, as well as innovative solutions to problems, and ideas for innovations in general, which can be comparable or even better than those provided by 'internal' firms' experts [4,29,42]. This has motivated government organizations to start taking advantage of this collective wisdom of the citizens, in order to develop better, more acceptable and effective public policies.…”
Section: Introductionmentioning
confidence: 99%